x:0.75=21分之4:x:5分之2=3分之1:9分之7
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 16:01:04
x:0.75=21分之4:x:5分之2=3分之1:9分之7x:0.75=21分之4:x:5分之2=3分之1:9分之7x:0.75=21分之4:x:5分之2=3分之1:9分之7
x:0.75=21分之4:x:5分之2=3分之1:9分之7
x:0.75=21分之4:x:5分之2=3分之1:9分之7
x:0.75=21分之4:x:5分之2=3分之1:9分之7
5分之2x+21=4分之3x
x:0.75=21分之4:x:5分之2=3分之1:9分之7
4分之x-6-x=2分之x+5
5分之x+4-(x-5)=3分之x+3-2分之x-2
5分之(X+4)-(X-5)=3分之(X+3)-2分之(X-2)
2分之x-4分之3-4x=2-x-8分之5-3x
5分之x+4-(x-50)=3分之x+3-2分之x-2
2分之x+4-x+5=3分之x+3-6分之x-2
x+5分之2=x分之1 x-4分之x-1=x-4分之3 2
24分之5x=8分之(3x-4)-2 3分之2x=9分之(4x-8)-5 49分之2x+3=7分之(4x-1)-21分之5
{x分之2-y分之3=4,x分之3+y分之6=5
5分之3x一7>=2分之x-2,4分之x一12分之2x一1>6分之1一3分之x
X+2分之X+3-X+4分之X+5=X+6分之X+7-X+8分之X+9,求X的值
3分之2x=12分之x平方+x平方分之3+x分之4
x+1分之2x=1 x-2分之x-x^2-4分之1=1 x+3分之5=x分之2 x-2分之6=x+3分之x -1
5分之4x=3分之2x+8
5分之2x-1=-4分之3+x
7分之4X-5分之1X=2